Manual for RERA Guidelines for Regulating Cross-border Power Trading in the SADC Region : A User's Guide - Castalia (World Bank, Washington, DC, 2013)
There are currently a large number of proposed cross-border generation and transmission projects in Southern Africa that are not moving forward, despite being technically and economically feasible. To help address this situation, the Regional Electricity Regulators Association of Southern Africa (RERA) has prepared a set of guidelines for national regulators in the SADC region, which have been adopted by the SADC Energy Ministers. This section of the Manual provides some context for the guidelines and provides an overview of the purpose and contents of the Manual.